E-Inventaris: Transformasi Digital Meningkatkan Efesiensi Pengelolaan Barang di SMAN 3 Pariaman - Kamilah, Balkis Putri; Sulvi, Arifa Rizka; Putri, Salmawati (Yayasan Lembaga Studi Makwa, 2024)
E-Inventory is a system designed to improve the efficiency of goods management at SMAN 3 Pariaman through the application of digital transformation. Digital transformation. With the development of information technology, efficient inventory management becomes very important to support the education process. education process. This research aims to evaluate the implementation of E-Inventory system and its impact on the management of goods in schools. Methods. include surveys and interviews with property management staff, as well as quantitative and qualitative data analysis. quantitative and qualitative data analysis. The results showed that the implementation of E-Inventory succeeded in reducing recording errors, speeding up the procurement and distribution process, and facilitates real-time stock monitoring. Monitoring in real-time. Thus, this system not only improves operational efficiency but also strengthens transparency and accountability in the management of goods at SMAN 3 Pariaman. In the management of goods at SMAN 3 Pariaman. The method used in This research is Research and Development (R&D), with the Waterfall model approach. Waterfall model This approach includes five main stages: communication, planning, and design. (communication, planning, modeling, construction, testing. (construction), testing. The advantages of this model include clear organization and comprehensive documentation, which makes project management easier. However, rigidity in the face of changing requirements and the time required to complete each stage can be a constraint. to complete each stage can be a constraint. Waterfall model is most effectively used in